Analisis Pemotongan, Penyetoran dan Pelaporan Pajak Penghasilan Pasal 23 pada PT. Wijaya Karya Beton Tbk PPB Sumatera Utara - Yudi Febrianto Samos; Novien Rialdy; Surya Sanjaya (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
One of the income taxes is Income Tax Article 23. In Income Tax Article 23 there is a process of withholding, depositing and reporting where if an error occurs in the process it can result in a shortfall in the amount of tax that should be deposited into the state treasury. Article 23 Income Tax Withholders are parties who pay income, namely government bodies, domestic corporate tax subjects, activity organizers, permanent establishments and other overseas representatives. This research was conducted at PT. Wijaya Karya Beton Tbk PPB. The aim of this research is to analyze the deduction, deposit and reporting of Income Tax Article 23 at PT. Wijaya Karya Beton Tbk PPB North Sumatra. The analytical method used is the descriptive method. Based on the research results, PT. Wijaya Karya Beton has implemented Article 23 Income Tax deductions and reporting in accordance with applicable tax regulations but PT. Wijaya Karya Beton TBK PPb North Sumatra in the implementation of income tax payment article 23 there are still things that are not on time, namely exceeding the deposit limit specified in Law Number 36 of 2008 concerning income tax article 23. In this research it can be concluded that PT. Wijaya Karya Beton has carried out its obligations properly in carrying out deductions and reporting Income Tax Article 23 and it is best that in carrying out the payment of income tax article 23 not exceed the deposit limit specified in Law Number 36 of 2008 concerning income tax article 23.